Spacery, koncerty i... "tubylcze wioski". O (dwuznacznych) przyjemnościach oferowanych w ogrodzie restauracyjnym poznańskiego Zoo w XIX i na początku XX wieku - Kurek, Krzysztof; Mateusz, Mayer (Wydawnictwo "Poznańskie Studia Polonistyczne", 2017)
Public walks, concerts and … ”villages of the natives”. On some (ambiguous) pleasures offered in the restaurant garden at Poznań Zoological Gardens in the nineteenth and the beginning of the twentieth century. The present article, based on richly detailed source material and search queries, presents questions related to “entertainment packages” offered by the restaurant gardens at Poznań zoological gardens since the 1870s and the early years of the twentieth century. One of the original attractions of the restaurant garden was musical concerts prepared on a regular basis by the musicians of the Poznań military garrison – the orchestra of the 46th and 47th Infantry Regiments and the 6th Grenadiers Regiment. Guest appearances of the performers that visited the venue included such famous and much-admired musicians as the orchestras conducted by Eduard Strauss (1889, 1891 and 1898) and Johann Strauss (1900, 1913 and 1914), among others. A particular complement to some of the then dancing and musical evenings was also displays of fireworks and the so-called “aeronautical games” with balloons filled with gas. Towards the end of the nineteenth century the restaurant gardens at the Zoo became a venue for public presentations of shows known as ”ethnological expositions”, ”villages of the natives” or “Peoples Shows”, as it was termed in Germany, that, from today’s perspective were blatantly racist and still lead to some embarrassment and raise moral doubts, though at the time, i.e. from the 1870s, were a common-place phenomenon in the entertainment business targeted at mass audience in Western Europe. As late as the first decade of the twentieth century, watching ”exotic indigenous peoples” with their intriguing customs was an extremely popular form of mass entertainment in Europe, which was reflected, for example, in the successive editions of exhibitions of exotic populations during the World’s Fairs. Even though the surviving sources clearly indicate that Poznań displays were not staged behind a fence, with natives near or locked up in cages, but rather in special tents set up on the gardens’ premises, still the convention adopted by the organisers of exhibitions of indigenous populations from various parts of the globe depicted as savages as well as the surrounding physical space of the zoological gardens have since been criticized and ascertained as highly degrading and racist. Contemporary anthropologists and researchers even refer to these ethnological expositions as the so-called human zoos. It obviously cannot be overlooked or disregarded that showing people on display as article of curiosity was instrumental and clearly gain-motivated exploitation of people who represented different cultures and the world of values totally incomprehensible for the majority of passers-by who lined up to see them as the major attraction. The shows organized in Poznań were usually theme-based and included specially prepared spectacles, announced earlier by the local press (e.g. hunting, dances, caravan or fighting). The language itself that was used in the press reviews and accounts published in the contemporary Polish and German newspapers resonated in fact the Eurocentric point of view reflecting a tendency to interpret the world in terms of European values and experiences and showed a strong sense of racial and cultural superiority. The authors of the present article, drawing on the accounts published in the then Poznań-based newspapers, discuss the individual exhibitions of exotic populations brought from Africa, Asia, North America, Australia and New Zealand. The present study is the first publication based on detailed exploration of the available source material that reveals and discusses this unarticulated element of the history of Poznań.
Jest to pierwszy w dotychczasowych badaniach nad dziejami Poznania artykuł przedstawiający w tak obszerny sposób praktyki związane z funkcjonowaniem w ogrodzie restauracyjnym poznańskiego Zoo widowisk określanych mianem „wystaw etnologicznych”/ „tubylczych wiosek. Całość rozważań oparta została na rozległych kwerendach prasowych, z których wyłania się wstydliwy i dotychczas pomijany przez historyków wątek.
Keywords: history of Poznań in the 19th and the 20th century; history of the Zoological Gardens in Poznań; human zoo; colonialism